Security analysis of the OpenID Connect protocol integration with an OpenStack cloud using an external IdP - Batista G.C.* (2017)
© 2016 IEEE.Several Internet services require different pairs of usernames and passwords in order to authenticate their users. The password management process is time consuming and sus-ceptible to security issues. Moreover, cloud computing solutions already run into related problems. Single Sign-On is a way to handle all the multiple accounts that a user may have and OpenID Connect has a great adoption as a Single Sign-On solution. As well as OpenID Connect, OpenStack is growing as a cloud software due its large community and because its open source code. In this sense, our goal is to analyze the security aspects related to the usage of OpenID Connect, a single sign-on mechanism, in cloud computing solutions based on OpenStack using a external Identity Provider.